Sulfur-Mediated Synthesis of 2-Aryl-4(3H)-quinazolinones from 2-Aminobenzamides and Aryl Alcohols via KOtBu-promoted Oxidative Condensation - Vo, Ngoc Binh; Nguyen, Le Thanh Hang; Nguyen, Le Anh; Le, Dang Quang; Ngo, Quoc Anh (Synlett, 2025)
Here, we report a simple protocol for the oxidative cyclization of 2-aryl-4(3H)-quinazolinones from 2-aminobenzamides and aryl alcohols promoted by KOtBu, with S8/DMSO as the oxidant. This reaction has advantages such as easy-to-find starting materials, stability, and can be carried out under simple heating conditions without requiring transition metal catalysts, and is scalable. This method shows good tolerance to functional groups, including halogen, methoxy, and trifluoromethyl groups, as well as heterocyclic rings such as thiophene and pyridine in moderate to high yields (up to 92% yield). Furthermore, control experiments showed that the key step of this reaction involves the dehydrogenation of benzyl alcohol by an active sulfur species to the benzaldehyde intermediate, followed by oxidative condensation with 2-aminobenzamide.
Keywords: Sulfur; Quinazolinones; 2-Aminobenzamides; Aryl alcohols; Potassium tert-butoxide; Oxidative condensation